Physiological and Yield Responses of Pepper (Capsicum annuum L.) Genotypes to Drought Stress - Theodora Ntanasi; Ioannis Karavidas; Dimitrios Savvas; George P. Spyrou; Evangelos Giannothanasis; Beppe Benedetto Consentino; Vasileios Papasotiropoulos; Leo Sabatino; Georgia Ntatsi (Plants, 2025)
Drought stress is a critical abiotic constraint on agricultural productivity, particularly affecting crops like pepper (Capsicum annuum L.), which are highly susceptible to water deficits due to their physiological characteristics. The present study investigated the impact of a 40% reduction in irrigation on yield, macronutrient concentrations, and fruit quality across several pepper genotypes. The cultivars evaluated included two landraces, namely ‘JO109’ and ‘JO204’ (Capsicum annuum var. grossum), as well as the California cultivar ‘Yolo Wonder’ and the commercial F1 hybrid ‘Sammy RZ’, which served as controls. The experiment was conducted at the greenhouse facilities of the Laboratory of Vegetable Production, Agricultural University of Athens. Under reduced irrigation, most of the cultivars studied exhibited a decline in yield, which was attributed to a decrease in fruit number in ‘Yolo Wonder’ and a reduction in fruit weight in both ‘JO204’ and ‘Sammy’. In contrast, the landrace ‘JO109’ exhibited consistent yields under both growing conditions, a response likely attributed to elevated K concentration in the leaves and lower Na accumulation in the fruit, indicating enhanced tolerance to water deficit. A decline in leaf K concentration was observed in response to drought stress, while concomitantly increased concentrations of Na, Ca and Mg were recorded. Among fruit macronutrients, only Ca showed a significant decrease under reduced irrigation. Furthermore, fruit firmness (FF), titratable acidity (TA) and total soluble solids content (TSSC) exhibited higher levels under drought stress, particularly in ‘JO109’, while TA remained unaltered. These findings highlight the potential of landraces such as ‘JO109’ to be utilized in breeding programs aimed at enhancing resilience, while maintaining pepper fruit quality under limited water availability.